2009
DOI: 10.1163/156856209x453006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sericin with Variable Amino-Acid Content from Different Silk Strains on the Production of Collagen and Nitric Oxide

Abstract: Although silk sericin (SS) enhances the growth and attachment of fibroblast cells, its toxicity remains questionable. We investigated the effect of SS extracted by heat with variable amino-acid content on in vitro collagen promotion and nitric oxide synthesis. After 24 h of incubation, SS, especially from the Chul 1/1 strain which has the most methionine and cysteine content, enhanced fibroblast growth. The molecular mass of heat-extracted SS from these three strains showed a slightly different range, but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 36 publications
9
64
0
Order By: Relevance
“…It has been reported that sericin can induce collagen production 23,24) and promote fibroblast proliferation without the activation of pro-inflammatory cytokines, 23,25) and Aramwit and Sangcakul 32) showed that the topical application of sericin enhances wound healing rate and produces a woundsize reduction in rats. We also reported that sericin has a potent effect in promoting the corneal wound healing rate in rats, probably by increasing cell movement and proliferation in corneal epithelial cells.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that sericin can induce collagen production 23,24) and promote fibroblast proliferation without the activation of pro-inflammatory cytokines, 23,25) and Aramwit and Sangcakul 32) showed that the topical application of sericin enhances wound healing rate and produces a woundsize reduction in rats. We also reported that sericin has a potent effect in promoting the corneal wound healing rate in rats, probably by increasing cell movement and proliferation in corneal epithelial cells.…”
Section: )mentioning
confidence: 99%
“…19) Besides acting as a natural moisturizing agent, sericin also possesses anticoagulating, antioxidant, antiwrinkle, and antibacterial activities, and enhances the proliferation of mammalian cells in serum-free media. [20][21][22] In addition, sericin can induce collagen production 23,24) and promote fibroblast proliferation 23) without the activation of pro-inflammatory cytokines. 25) In this study, we undertook kinetic analyses of skin wound healing in normal rats and diabetic model rats, streptozotocininduced diabetic rats (STZ rat).…”
mentioning
confidence: 99%
“…Sericin is non-toxic to fibroblast cells. Methionine and cysteine content in silk sericin are important factors to promote cell growth and collagen synthesis [91]. Water-soluble silk sericin has no immunogenicity and is also a biocompatible macromolecular protein like silk fibroin [92].…”
Section: Sericinmentioning
confidence: 99%
“…Sericin was indicated to suppress lipid peroxidation and tyrosinase inhibitory activity (Kato et al, 1998). In addition to antioxidant activity and chemopreventive effects of sericin was found (Fan et al, 2009;Zhaorigetu et al, 2003), Silk sericin from silkworm cocoons accelerates the proliferation of mammalian cell line (Terada et al, 2002;Aramwit et al, 2009;Aramwit and Sangcakul 2007). Another study reported anti-cancer effects of sericin in colon cancer (Kaewkom et al, 2012).…”
Section: Cytotoxicity Assay Of Cocoon Extractsmentioning
confidence: 99%